2021
DOI: 10.3390/pathogens10060673
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Solutions to Viral Diseases of Finfish in Marine Aquaculture

Abstract: Aquaculture is the fastest food-producing sector in the world, accounting for one-third of global food production. As is the case with all intensive farming systems, increase in infectious diseases has adversely impacted the growth of marine fish farming worldwide. Viral diseases cause high economic losses in marine aquaculture. We provide an overview of the major challenges limiting the control and prevention of viral diseases in marine fish farming, as well as highlight potential solutions. The major challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 192 publications
(166 reference statements)
0
13
0
Order By: Relevance
“…Viral whole-genome sequencing has become a routine and cost-effective scientific approach that has gained much prominence during the human COVID-19 pandemic. Considering the extensive commercial importance of salmon aquaculture, balanced against the scale of financial, welfare, and reputational costs caused by viral diseases, we argue that efforts are required to develop and sustain routine viral genomic surveillance programs as part of the 'toolbox' to limit viral disease outbreaks [8]. Data such as that reported here, ideally expanded in spatial and temporal resolution, can be used by producers and regulating authorities to support a range of actions aimed at disease control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral whole-genome sequencing has become a routine and cost-effective scientific approach that has gained much prominence during the human COVID-19 pandemic. Considering the extensive commercial importance of salmon aquaculture, balanced against the scale of financial, welfare, and reputational costs caused by viral diseases, we argue that efforts are required to develop and sustain routine viral genomic surveillance programs as part of the 'toolbox' to limit viral disease outbreaks [8]. Data such as that reported here, ideally expanded in spatial and temporal resolution, can be used by producers and regulating authorities to support a range of actions aimed at disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Viral pathogens pose a particular challenge due to limited effective treatment options, coupled with the fact that outbreaks are highly damaging financially and in terms of animal welfare. A range of approaches are available to prevent and control viral disease in aquaculture [8], including selective breeding [9] and vaccination for finfish [10]. While it is recognized that genomic epidemiology can deliver much to support disease control efforts in aquaculture [11] and other sectors [12], large-scale genomic sequencing to monitor aquaculture pathogens is not a widespread practice, even for high-value species.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivated viral vaccines are safe and won’t cause any infections because the virus has lost its activity, many inactivated aquatic viral vaccines have been reported in studies ( Table 5 ). However, the immune response is lessened or the duration of immunity is reduced since the virus is only a fragment and not an intact virus ( 173 ). It has been reported that the infectious hematopoietic necrosis virus (IHNV) vaccine inactivated by 1.5 mmol/L Beinylating agents can significantly improve the survival rate of rainbow trout ( 155 ).…”
Section: Classification and Preparation Technology Of Aquatic Vaccinesmentioning
confidence: 99%
“…Pathogens pose extreme risks to abalone and other molluscs, offsetting aquaculture production as a result, which accounts for one third of global food production [9][10][11]. It is estimated that $2B US of aquaculture production is lost per year, with viruses being a major contributor to this figure [9][10][11]13]. Specifically, 10% of reared aquaculture species are lost due to pathogens each year, 90% of which pertain to viruses or bacteria [14].…”
Section: Introductionmentioning
confidence: 99%